2018
DOI: 10.1016/j.jamcollsurg.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Survival in Patients with Bile Leak and Ductal Injury: Management Strategy and Outcomes

Abstract: BACKGROUND The increased incidence of bile duct injuries (BDIs) after the adoption of laparoscopic cholecystectomy has been well documented. However, the longitudinal impact of bile leaks and BDIs on survival and healthcare use have not been studied adequately. The aims of this analysis were to determine the incidence, long-term outcomes, and costs of bile leaks and ductal injuries in a large population. STUDY DESIGN The California Office of Statewide Health Planning and Development database was queried from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 28 publications
3
56
0
3
Order By: Relevance
“…On the contrary, the rate of bile leak has increased in recent decades (1.5% to 3%) [4,11]. In the present study, the rate of bile leak and major duct injury was 0.43% and 0.35%, respectively, which is in line with the published international standard [5].…”
Section: Minimally Invasive Surgerysupporting
confidence: 90%
See 2 more Smart Citations
“…On the contrary, the rate of bile leak has increased in recent decades (1.5% to 3%) [4,11]. In the present study, the rate of bile leak and major duct injury was 0.43% and 0.35%, respectively, which is in line with the published international standard [5].…”
Section: Minimally Invasive Surgerysupporting
confidence: 90%
“…It significantly increases the morbidity, mortality, and costs of hospital stay and decreases the quality of life [5,9]. Furthermore, it is associated with litigations.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing use of LC was reported as being associated with higher rates of LC associated bile duct injuries (BDIs), although recent population-based studies suggest the incidence of BDI has returned to open cholecystectomy rates. 1,2 The overall incidence of BDI in South Africa is not known. In the only report on outcomes after LC in a South African population to date, Mbatha et al found an incidence of 1.2% for major BDIs in a single centre retrospective review of LCs over an 18-month period.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate closure of the cystic duct is essential to prevent CDL, especially in patients with complicated gallstone disease having a higher risk of bile leakage. Although CDL is classified as a minor injury of the bile ducts, it is associated with significant re-intervention rate, increased morbidity and even mortality[ 6 - 8 ]. The most common closure technique during LC is by simple (non-locking) metallic clips.…”
Section: Introductionmentioning
confidence: 99%